Ring finger 220 promotes the stemness and progression of colon cancer cells via Ubiquitin specific peptidase 22-BMI1 axis. Issue 2 (20th December 2021) - Yan, Jianwen; Tan, Min; Yu, Lin; Jin, Xichao; Li, Yangcheng
ABSTRACT: Colorectal cancer (CRC) is ranked as the third most common malignancy worldwide. Therefore, it is urgent to screen novel and effective molecular drug targets for colorectal cancer therapeutics. In this study, the specific role and related mechanism underlying Ring finger (RNF) 220 in colon cancer were investigated. Firstly, RT-PCR assay was used to compare differences between expression levels of RNF220 in colorectal tumor and normal tissues. Western blot and RT-PCR assays were applied to examine the protein levels of RNF220 in normal colonic mucosa and colorectal cancer cells. We found that RNF220 was upregulated in colorectal cancer in patients and cell models. RNF220 promoted the proliferation and migration, invasion of colorectal cancer cells through BrdU incorporation, clone formation, transwell and wound healing assays. Spheroid formation and western blot assays illustrated that RNF220 promoted the stemness of colorectal cancer cells. Moreover, we found that RNF220 regulated BMI1 expression through USP22 by western blot. Finally, we discovered that RNF220 facilitated tumor growth in vivo through establishment of subcutaneous xenograft tumor mice model. In conclusion, RNF220 promoted the stemness and progression of colon cancer cells via the USP22-BMI1 axis.